The search for stable and efficient sonoelectrocatalysts for oxygen reduction and hydrogen peroxide formation: azobenzene and derivatives - Sljukic, B; Banks, C; Compton, R (2004)
We report the electrochemical reduction of oxygen using glassy carbon electrodes modified with azobenzene, hydroazobenzene. or fast black K salt (2.5-dimethoxy-4-[(4-nitrophenyl)azo] benzenediazonium tetrachlorozincate). The performance of the electrodes under ultrasound was explored. At the highest intensity (87 W cm-2) with one hour continuous insonation, voltammetric signals for azobenzene decreased by 7%, hydroazobenzene by 9% and fast black K by 18%. The catalytic rate constants of the immobilised species towards oxygen reduction were assessed via cyclic, rotating disc and sono-voltammetry. The rate constants were found to be 6.1 × 103 M-1 s-1 for azobenzene, 7.4 × 103 M -1 s-1 for hydroazobenzene and 10.4 × 103 M-1 s-1 for fast black K. These values suggest the use of these modified electrodes as practical hydrogen peroxide generators.